"CinNapht" dyes: a new cinnoline/naphthalimide fused hybrid fluorophore. Synthesis, photo-physical study and use for bio-imaging. Issue 48 (8th September 2021) - Hoang, Minh-Duc; Bodin, Jean-Baptiste; Savina, Farah; Steinmetz, Vincent; Bignon, Jérôme; Durand, Philippe; Clavier, Gilles; Méallet-Renault, Rachel; Chevalier, Arnaud
Abstract : Six-membered-diaza ring of cinnoline has been fused on naphthalimide dye to give a donor–acceptor system called CinNapht. Abstract : Six-membered-diaza ring of cinnoline has been fused on naphthalimide dye to give a donor–acceptor system called CinNapht. This red shifted fluorophore, that can be synthesised in gram scale, exhibits a large Stoke shift and a fluorescence quantum yield up to 0.33. It is also characterized by a strong solvatochromic effect from green to red emission as well and can be used for bio-imaging.